Postpartum thiamine deficiency in a Karen displaced population. - Mcgready, R; Simpson, J; Cho, T; Dubowitz, L; Changbumrung, S; Böhm, V; Munger, R; Sauberlich, H; White, N; Nosten, F (2001)
BACKGROUND: Before its recognition, infantile beriberi was the leading cause of infant death in camps for displaced persons of the Karen ethnic minority on Thailand's western border. OBJECTIVE: This study aimed to document thiamine status in the peripartum period to examine the current supplementation program and the correlation between the clinical manifestations of thiamine deficiency and a biochemical measure of thiamine status. DESIGN: Women were enrolled prospectively at 30 wk of gestation and were followed up weekly until delivery and at 3 mo postpartum. Thiamine supplementation during pregnancy was based on patient symptoms. RESULTS: At 3 mo postpartum, thiamine deficiency reflected by an erythrocyte transketolase activity (ETKA) > or = 1.20% was found in 57.7% (15/26) of mothers, 26.9% (7/26) of whom had severe deficiency (ETKA > 1.25%). No significant associations between ETKA and putative maternal symptoms or use of thiamine supplements were found. CONCLUSIONS: Biochemical postpartum thiamine deficiency is still common in Karen refugee women. This situation may be improved by educating lactating women to reduce their consumption of thiaminase-containing foods and by implementing an effective thiamine supplementation program.